PENURUNAN STRES KLIENCA MAMAE MELALUI GUIDED IMAGERY RELAXTION DAN FAMILY PSYCHOEDUCATION THERAPHY DI RSUP.RD.M.DJAMIL PADANG - Renidayati, Renidayati (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
An increase in Ca Mamae patients every year. This has an impact on the patient's psychologicalproblems. Stress is one of the psychological reactions that arise when a person is diagnosed withcaesarean cancer. One of the non-pharmacological therapies that can be used to overcome stress isguided imagery.The guided imagery was combined with family psychotherapy education. The studyaimed to determine the reduction in stress in patients with ca. mamae through the implementationof guided imagery and therapy for family psychoeducation therapy. Research design